Advanced control of a reformer based fuel cell system coupled with multiple, uncertain renewable energy sources and an energy storage system. (2020) - P S, Pravin; Misra, Shamik; Bhartiya, Sharad; Gudi, Ravindra D.
Abstract: This paper focuses on integration of uncertain renewable energy sources along with relatively deterministic energy sources such as reformer based fuel cell and battery. The power mix scenario between these multiple renewable energy sources along with the reformer based fuel cell system coupled with an energy storage option, is envisaged to ensure undisrupted power supply and to combat the intermittent nature of these renewable sources. To demonstrate this scenario, a decision support system that provides an optimal decision of the power mix over a particular horizon is assumed to be available. A model predictive control scheme is deployed at the lower level control layer, to maintain the overall plant operation, and to make optimal decisions to choose the right combination of the available power sources both in the absence and presence of uncertainties in the renewable energy sources. During real time operation of the plant, due to the uncertainties in the contribution of power from solar and wind sources, the demand to the fuel cell as well as the charging and discharging profiles of the battery deviates from that planned in the upper level scheduling layer. The ability of the designed MPC to track the target power profile and to reliably overcome the uncertain behavior of the renewable energy sources by appropriately choosing between the reformer based fuel cell and the battery unit is demonstrated in this paper.